2011
DOI: 10.1038/ijo.2011.179
|View full text |Cite
|
Sign up to set email alerts
|

Is the burden of overweight shifting to the poor across the globe? Time trends among women in 39 low- and middle-income countries (1991–2008)

Abstract: Background Overweight prevalence has increased globally; however, current time trends of overweight by social class in lower income countries are unknown. Methods We used repeated cross-sectional, nationally representative data from the Demographic and Health Surveys on women aged 18–49 with young children (n=421,689) in 39 lower income countries. We present overweight (body mass index ≥25) prevalence at each survey wave, prevalence difference and prevalence growth rate for each country over time is presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
138
4
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(163 citation statements)
references
References 20 publications
15
138
4
6
Order By: Relevance
“…No empirical studies have focused on investigating the relationship between different indicators or how these associations diverge by level of economic development for different indicators, although in a previous study, we have demonstrated an interaction between education and occupation in older Chinese women [31]. The findings in this study corroborate the existence of a changing SES-obesity association dependent on a country's level of economic development [3,4,5,6]. However, two studies claim that DHS data do not provide any evidence of an SESoverweight/obesity reversal [7,8].…”
Section: Comparison With Prior Studiessupporting
confidence: 80%
See 3 more Smart Citations
“…No empirical studies have focused on investigating the relationship between different indicators or how these associations diverge by level of economic development for different indicators, although in a previous study, we have demonstrated an interaction between education and occupation in older Chinese women [31]. The findings in this study corroborate the existence of a changing SES-obesity association dependent on a country's level of economic development [3,4,5,6]. However, two studies claim that DHS data do not provide any evidence of an SESoverweight/obesity reversal [7,8].…”
Section: Comparison With Prior Studiessupporting
confidence: 80%
“…Accessed 2013 Jan 1) are a key source of data for studies on obesity [4,5,6,7,8,17,18,19]. They are a worldwide project funded by the United States Agency for International Development aiming to provide data on demographics and health outcomes, mainly for women and young children.…”
Section: Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…While overweight and obesity in developing countries are positively associated with income, poor population segments are also increasingly affected (Jones- Smith et al, 2012;Roemling and Qaim, 2012). These effects of the nutrition transition on body weight have primarily been observed in adult populations.…”
Section: Dietary Trends and Child Nutrition: Expected Relationshipsmentioning
confidence: 99%